Haptic Keyclick Feedback Improves Typing Speed and Reduces Typing Errors on a Flat Keyboard - Ma, Zhaoyuan; Edge, Darren; Findlater, Leah; Tan, Hong Z (2015 IEEE World Haptics Conference (WHC), 2015)
The present study used a flat keyboard without moving keys and enabled with haptic keyclick feedback to examine the effect of haptic keyclick feedback on touch typing performance. We investigated, with well-controlled stimuli and a within-participant design, how haptic keyclick feedback might improve typing performance in terms of typing speed, typing efficiency and typing errors. Of the three kinds of haptic feedback we tested, all increased typing speed and decreased typing errors compared to a condition without haptic feedback. We did not find significant differences among the types of haptic feedback. We also found that auditory keyclick feedback alone is not as effective as haptic keyclick feedback, and the addition of auditory feedback to haptic feedback does not lead to any significant improvement in typing performance. We also learned that global haptic keyclick feedback simulated through local keyclick feedback on each key (as opposed to haptic feedback all over the keyboard) might have the additional and unexpected benefit of helping a typist to locate keys on a keyboard. Furthermore, the participants preferred auditory or haptic keyclick feedback to no feedback, and haptic feedback restricted to the typing finger alone is preferred to that over a larger area of the keyboard.